2018
DOI: 10.3928/23258160-20180501-05
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness as a Potential Predictor of Clinical Response to Stereotactic Radiotherapy for Neovascular Age-Related Macular Degeneration

Abstract: Baseline SFCT may help predict which patients with nAMD will respond more favorably to SRT. The authors found eyes with a thicker baseline SFCT needed fewer IVIs after SRT. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:320-328.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this post hoc analysis, we investigated the predictive value of choroidal substructure analysis for treatment response to SRT in nAMD patients. While we previously demonstrated that subfoveal CT can be a good baseline indicator to predict SRT outcome, this study is the first to report the impact of each of the three choroidal vascular layers as well as the combination of all these choroidal metrics in this context 10 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In this post hoc analysis, we investigated the predictive value of choroidal substructure analysis for treatment response to SRT in nAMD patients. While we previously demonstrated that subfoveal CT can be a good baseline indicator to predict SRT outcome, this study is the first to report the impact of each of the three choroidal vascular layers as well as the combination of all these choroidal metrics in this context 10 …”
Section: Discussionmentioning
confidence: 90%
“…Informed consent was obtained from all individual participants included in the study. The methodology has been reported elsewhere 10 . Briefly, medical records were screened for patients with treatment-experienced nAMD, who, in addition to pro re nata IVIs, received SRT and had at least 12 months of complete follow-up afterwards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been found that stereotactic radiotherapy (SRT) can reduce the number of repetitive intravitreal injections (IVIs) in patients with neovascular AMD as a new adjuvant treatment. Ranjbar et al [ 64 ] used EDI-OCT to measure SFCT and central macular thickness (CMT) in patients with neovascular AMD who received SRT and one mandatory IVI and followed up for at least 12 months. The results showed that the annual injection rate decreased from 6.86 before SRT to 3.46 afterward, and the SFCT and CMT decreased 37 μ m and 71 μ m, respectively, compared with baseline at 12-month follow-up.…”
Section: Evaluation Of Therapeutic Effect In Macular Diseasesmentioning
confidence: 99%